Portfolio selection and primary user QoS guarantee based resource allocation in cognitive radio networks - Hui LIANG; Xiao-hui ZHAO (Tongxin xuebao)
Inspired by portfolio selection theory,an efficient primary user QoS guaranteed resource allocation algorithm from secondary user interference by using historical channel state information was proposed.This algorithm formulates the risk as optimization objective,and restricts the interference which comes from secondary system to primary users below a mutual interference threshold.Then quadratic programming method is used to solve this optimization problem.Finally,performance comparison between the original algorithm without protection and the proposed algorithm was given.Simulation results illustrate that the proposed algorithm can minimize secondary system risk under an expected transmission rate and guarantee primary user’s QoS.